Bladder Cancer Management of NMI and Muscle-Invasive Cancer - Hammad Ather, M. (IntechOpen, 2017)
Bladder cancer is one of the most exciting urological cancers. It exists in two forms - non-muscle-invasive (NMI) and muscle-invasive (MI) disease. The difference in the clinical picture has been the focus of significant research in defining the molecular characteristics of urothelial cancer (UC) of the bladder. This book provides an overview of the most hotly debated areas in bladder cancer. Authors have focused on the emerging role of markers for NMI UC and various ways of improving the efficacy of current chemotherapy in the first section. The second section has focused on the surgical aspects of MI UC. Two major areas of debate - the role of pelvic lymph node dissection and genital sparing surgery - are discussed in this section.